Fundamentals of Entrepreneurship (ENT300) : Deisy Valet / Hazra Afira Marzuki … [et al.] - Marzuki, Hazra Afira; Apon, Loviana Mei; Abdul Rahman, Mohd Shafiq; Abdul Ghani, Nurhafieza; Zaidi, Zarith Tihani Nabihah (2018)
“Deisy Valet” is a business company which focusing on garments that are in line with current trend. The mission of our valet is to be the best and be known all around the world and on par with other famous brands by offering the best products. Our business “Deisy Valet” is a partnership business which consist of five people. To start the business, each member had contributed RM15,000 as stated in the partnership agreement. “Deisy Valet” is a boutique selling trendy clothes, accessories and scarves which every working women and teenagers, especially students had always wanted. The business was formed on 1st January 2018. Our boutique is located at the first floor of Summer Mall, Kota Samarahan.